Characterization of Molasses Spent Wash and its decolorization using Mushroom Cultivation - Vaishali A. Pawar; Pooja J. Bhangare; Yogesh P. Lolage; Mayuri J. Bhalekar (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Molasses spent wash is a by-product of sugar cane, sugar beet and citrus industries. Molasses contains mixture of uncrystallizable sugar and non-sugar components. It is one of the most difficult waste products to dispose due to its acidic pH, dark brown colour, high ash content, high percentage of dissolved organic and inorganic matter.Molasses spent wash is one of the major components of growth media used in many industrial processes but presence of melanoidin, a recalcitrant compound causes several toxic effects on the living system. This is an attempt to study the Physico-chemical characteristics, microbial screening of molasses spent wash and use of mushroom in the decolorization of molasses spent wash. It was seen that mushroom spawn showed better growth on medium prepared in100% molasses spent wash as compared to 75%, 50% and 25% and also reduced its dark brown colorization.